An Unusual Case of Cerebellar Tonsillar Descent till C7 Vertebrae in a Case of Chiari Malformation with Meningomyelocele - Acharya, Abhijit; Mahapatra, A. K.; Tripathy, Soubhagya; Panigrahi, Souvagya; Deo, Rama Chandra; Senapati, Satya Bhusan; Begum, Mehnaj (Indian Journal of Neurosurgery, 2024)
Arnold–Chiari or Chiari malformations are a group of posterior fossa malformations that include the pons, medulla, and cerebellum. This group of disorders may consist of associated abnormalities like myelomeningocele and encephalocele. Chiari malformation has been classified majorly into four categories. Chiari I malformation has been defined as tonsillar descent more than 5 mm below the level of the foramen magnum. The maximum descent of tonsillar herniation reported is 27 mm below the foramen magnum around the C2 vertebrae. In this study, we report the case of a 4-month-old infant with swelling over the lumbosacral (LS) spine since birth with a gradually progressive increase in head size since the age of 2 months. The infant had occasional stridor with respiratory distress for 2 months. Magnetic resonance imaging (MRI) of the brain and spine revealed gross hydrocephalous with myelomeningocele at the L1–L5 level with associated Chiari malformation. The tonsillar descent was almost at the level of C7, which was unusual in his patient. The infant underwent a right ventriculoperitoneal shunt placement and myelomeningocele repair. It was decided that the malformation would be managed in the second sitting. The postoperative period was uneventful and the respiratory distress improved. Cases of tonsillar descent (Chiari I malformation) to the C7 vertebral level are very rare.
Keywords: Chiari malformation; myelomeningocele; cerebellar tonsillar herniation